Representasi Dogma Orang Tua dalam Film Ngeri-Ngeri Sedap: Analisis Semiotika Roland Barthes - Affandi Salim Lubis; Rahmat Hidayat (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
Films not only function as entertainment media, but also as cultural texts that represent values, ideologies, and social relations in society. This study aims to reveal the representation of the dogma "parents are always right" and "children as the successors of family honor" in the film Ngeri-Ngeri Sedap, and to show how the film simultaneously reproduces and critiques the ideology of the Batak patriarchal family. The novelty of this research lies in a critical reading of the film's ideological ambivalence, namely between the naturalization of cultural values ​​and children's resistance to parental authority. This study uses a qualitative approach with Roland Barthes's semiotic analysis method that includes the levels of meaning of denotation, connotation, and myth. The unit of analysis in this study is selected scenes that display the power relations between parents and children in the context of Batak families. Data were collected through non-participant observation and film documentation. The results show that the dogma "parents are always right" is represented through the dominant and authoritative figure of Pak Domu in determining his children's life choices. Meanwhile, the dogma "children as the successors of family honor" is evident in the demands on children to maintain the clan, work, and family responsibilities. At the mythical level, the film normalizes the values ​​of filial obedience and family honor as normal within the Batak social structure. However, the film also presents symbolic resistance through critical attitudes, humor, and children's rejection of parental dominance. These findings contribute to the study of media semiotics by demonstrating that films not only reproduce cultural ideologies but also serve as a space for value negotiation between tradition and the individuality of the younger generation.